(untitled) (Research, Society and Development, 2023)
The escalating consumption of non-renewable energy sources has a direct and adverse impact on environmental sustainability, leading to detrimental effects such as global warming, acid rain, biodiversity loss, and energy source depletion. The current high energy demand and exorbitant taxation prices have prompted a growing need for sustainable and economically viable alternative energy sources. Among the various renewable technologies, solar photovoltaic energy has gained significant global recognition. This paper aims to outline the implementation of a photovoltaic solar system at Christus Faculdade do Piauí (CHRISFAPI), with the objective of fulfilling the institution’s energy requirements, the study encompasses the design and sizing of the photovoltaic system, along with cost estimation and financial returns. The methodology employed involved analyzing the electricity consumption over a 12-month period, from January 2022 to December 2022. For the recently added unit, data was collected based on the number of devices and their operating durations. Based on this analysis, the viability of the project was evaluated, concluding that the proposed system would be able to adequately meet the energy demands of the units. Moreover, from an economic perspective, the project is deemed feasible and profitable, given its financial payback period.